Theory and research in educational administration - Hoy, Wayne K.; Miskel, Cecil G. (Research and theory in educational administration, 2002)
This series is dedicated to advancing our understanding of schools through empirical study and theoretical analysis. Scholars, both young and established, are invited to publish original analyses, but we especially encourage young scholars to contribute to Theory and Research in Educational Administration. This first issue provides a mix of beginning and established scholars and a range of theoretical perspectives. Eight separate but related studies were selected for this first issue.Three of the research pieces deal with the intended and unintended consequences of policy and political initiatives in schools. Do high-stakes accountability environments threaten the potential of learning organizations? Marks and Printy grapple with that question. Not surprisingly, they anticipate the latent dysfunctional consequences of high-stakes accountability as they provide a careful analysis of urban school district responses to state policies. Well-intended initiatives produced unintended consequences that threatened the capacity for organizational learning in these schools. In a similar fashion, Jones and Malen's findings suggest that political strategies that use insider dynamics can foster successful enactment of reforms but often at a cost of undermining efforts to implement the policy. Song and Miskel focus their analysis on national reading policy. An examination of national interests groups and policymakers suggests that an assessment of various groups' influence is necessary if policy actors are to make sensible judgments in choosing allies and building coalitions for effective actions.Two of the papers are informed by contingency theory. Ogawa and Studer are concerned with the relationship between the school and its community. They propose that both buffering and bridging strategies enable schools to deal with parents effectively. Because schools depend on parents for resources, they bridge to parents in cooperative fashion, but because parents often pose uncertainty, schools also buffer parent influence by limiting their access. Yet, there is divergence from contingency theory because schools depend primarily on parents to provide socio-cultural rather than material resources; hence, schools often use strategies that shape rather than diminish dependence on parents. Rowan, also draws ideas from contingency theory to examine the extent to which the nature of teachers' instructional work affects patterns of instructional management in schools. His data support the explanation that teachers who face increased task variety actively work to construct "organic" patterns of instructional management to reduce task uncertainty and to increase workplace motivation and commitment.Three papers examine teachers in schools. Rowan is intrigued by the variation in the nature of teachers' work both in terms of task variety and task uncertainty. He finds that teachers do not see their work as many organizational theorists do, that is, as a non-routine form of work; in fact, teachers view teaching as either as a routine task or "expert task." In spite of the fact that many teachers endorsed a constructivist view of teaching, few concluded it was a non-routine task. Moreover, teachers in different disciplines have different views about both the nature of academic knowledge and desirable teaching practices. Both Goddard and Hoy and his colleagues use social cognitive theory to develop an argument of the importance of collective efficacy in positively influencing student achievement. Hoy, Smith, and Sweetland build on their earlier work to demonstrate that collective efficacy of schools is pivotal in explaining student achievement in a sample of rural schools. Goddard shows that that collective efficacy is also an important predictor of the practice of involving teachers in important school decisions. He concludes that the more we learn how school practices are related to collective efficacy, the more we will know about what school leaders.